Материалы к изучению пластинчатоусых жуков (Coleoptera, Lamellicornia) Тбилиси и его окрестностей - Джамбазишвили, Я.С. (Вестник зоологии, 1970)
В 1965—1967 гг. автором были собраны в Тбилиси и его окрестностях пластинчатоусые жуки 91 вида относящиеся к 37 родам и трем семействам. Приводится их перечень и дается деление по зоогеографическим признакам. In 1965—1967 in Tbilisi and its environs 91 species of Lamellicornia belonging to 37 genera and 3 families were registered.
Zoogeographical analysis showed that 10 species (10.9%) belong to the Transpalearctic forms, 4 species (4.4%)—to the European Siberean forms. 13 species (14.3%)—to the Steppe forms, 21 species (23.1%)—to the Mediterranean (widely distributed) forms, 25 species (27.5%) —to the East Mediterranean, 11 species and subspecies (12.1) —to the endemics of the Caucasus, 2 species (2.2%)—to the Central Asia forms, 1 species (1.1%) — to the Southpalearctic-Indian forms.